Analysis of bending vibration characteristics of rotating composite boring bar. (August 2019) - Ren, Yongsheng; Zhao, Qi; Liu, Yinlei; Ma, Jingmin
Abstract: In this study, the dynamic characteristics of composite boring bar are theoretically investigated. The structural dynamic model of composite boring bar having clamped-free supports is developed by employing Bernoulli-Euler beam theory and considering dissipative characteristics of viscoelastic composite material. The Galerkin method is used to solve the equations of bending vibration. The complex characteristic equation for bending vibration is derived. Numerical examples present the variation of the natural frequency, damping and dynamic stiffness with ply angle, and the variation of the natural frequency and damping with rotating speed are also obtained. The study results show that ply angle, stacking sequences and ratio of length over outer radius have significant influence on the dynamic characteristics of composite boring bar. Conclusively, lamination design can significantly improve dynamic performance and enhance chatter stability in machining.